A Point of Two Mode-Session Logs Based Web User Interest Prediction System From Web Search Engine - Velmurugan, R; Victor, SP (International Journal of Computer Sciences and Engineering, 2025)
Information prediction from web search is a hands-off process based on user interest. By differently user may think based on the knowledge or relevant search things, but web mining tasks are complex to understanding the user behaviour and knowledge to retrieve the right things to the user. To propose a new intent interest prediction for improving the efficiency, we propose a session timing preference based two mode user interest prediction methods called semantic log pre-fetch clustering (SLCPC) algorithm and personalized feed ranking (FPR) algorithm to deduce a set of related categories for each user query based on the retrieval history of the user session, i.e. different contents have to be placed for different users according to the user relevant search profiles spending time on interested logs. Two modes analyse behaviours like time of visit, navigation URL, weblogs, and user actions on the webpage. SLPC predicts web log data of the user and also identifies the implicit behaviours performed by the user. The identified information is used to identify the user interest and seeds are generated by logging page. So the user doesn't wait for long more time to search our interesting factor frequently. The web users are clusters based on the feed ranking interest which is used continues searches. Our proposed system improves the accuracy of personalized user search compared to an existing approach.